Combating citrus decline in Arunachal Pradesh - Singh, Raghuveer; Kanjam, Valenta; Angami, T.; Wangchu, L. (Indian Horticulture, 2024)
Khasi mandarin (Citrus reticulata) is predominant fruit crop in Arunachal Pradesh and addressing citrus decline is vital for sustaining and enhancing citrus production in the state. In Arunachal Pradesh, combating citrus decline requires a multifaceted approach, combining cultural, biological, and chemical control methods, along with community engagement and policy support.